The influence of typical versus atypical ads on sharing intention - Rita, P.; Guerreiro, J.; Matos, S. (International Journal of Internet Marketing and Advertising, 2023)
Consumers are overwhelmed with advertising messages which makes some of them unable to break the clutter to be viewed and shared. The purpose of the current paper is to study how visual attention, arousal, and pleasure may lead to advertising sharing intention. This study followed an experimental design using consumer neuroscience methods, more specifically, eye tracking and electro dermal activity, evaluating how typicality and the celebrity factor can influence consumers' visual attention and arousal. Participants watched four ad campaign scenarios: a typical ad without celebrities (T), a typical ad with celebrities (TC), an atypical ad without celebrities (A), and an atypical ad with celebrities (AC), with arousal and pleasure being measured through the self-assessment manikin and their sharing intention through a questionnaire. Findings showed that atypical ads generate higher levels of arousal and pleasure, which positively influences sharing intention. Also, when comparing (TC) with (AC), the celebrity factor presents lower arousal levels in the TC scenario.